Recycling and Degradation Pathways of Synthetic Textile Fibers such as Polyamide and Elastane - Pilar Chavez‐Linares; Sandrine Hoppe; Isabelle Chevalot (Global Challenges)
Abstract Synthetic textile production is a major contributor to global waste growth, a phenomenon exacerbated by population growth and increased consumption. Global fiber production is expected to reach 147 million tons by 2030. New insights into recycling solutions are being developed. For example, progress has been made in recycling fibers such as polyester, including polyethylene terephthalate (PET), through the use of enzymes that can break specific bonds and return the material to its original state. However, this process must be carried out according to the nature of the polymer in question. In addition, the mixing of different synthetic fibers and the use of dyes make it difficult to develop a complete recycling process that separates the fibers and returns them to their original raw material. This review focuses on two types of fibers widely used in the textile industry, Nylon or polyamide (PA) and elastane (Spandex or Lycra), and explores the challenges and opportunities associated with their recycling.